Effect of mannan oligosaccharides on growth performance, intestinal structure and nonspecific immunity of tilapia, Oreochromis niloticus × O.aureus - LIU Ai-jun; LENG Xiang-jun; LI Xiao-qin; WANG Li-ping; WAN Hu (浙江大学学报. 农业与生命科学版)
Two experiments were conducted to investigate the effect of adding mannan oligosaccharides (MOS) in diets on growth performance, intestinal structure and serum nonspecific immune index of tilapia, Oreochromis niloticus × O. aureus. Diets containing MOS 0.00% (control group), 0.25%, 0.50%, 0.75% were fed to tilapia with initial bodyweight of (1.00 ± 0.04) g for 8 weeks (exp.Ⅰ), or fed to tilapia with initial bodyweight of (20.04 ± 0.13) g for 30 days (exp.Ⅱ). In both trials, growth rates of 0.50%,0.75% MOS group were significantly increased and feed conversion rate (FCR) was decreased compared with control group (P<0.05). In exp. Ⅱ, the height, width and density of intestinal villi, protease activities of intestine and stomach, dry matter digestibility, activity of serum superoxide dismutase (SOD), alkaline phosphatase (AKP) were significantly increased and intestinal wall thickness was significantly reduced by adding 0.25%, 0.50% and 0.75% MOS compared with control group (P<0.05). There was no difference in the number of goblet cells in intestinal villi among the four groups (P>0.05). Results above showed that proper level of MOS in diets could improve growth performance and intestinal structure of tilapia, increase nutrient digestibility and serum non-specific immune function. The MOS supplement in diets is suggested to be 0.50% for young tilapia.